Four philosophers and the bomb : Russell, Aron, Jaspers and Anders on atomic warfare - Castelli, Alberto, 1967-; Gatta, Giunia, 1971-; Latini, Micaela, 1973-; Raschi, Francesco (Routledge, 2025)
"In this book, Alberto Castelli, Giunia Gatta, Micaela Latini and Francesco Raschi examine how four prominent intellectuals of the twentieth century (Bertrand Russell, Karl Jaspers, Raymond Aron, and Günther Anders) understood the atomic warfare. With a chapter devoted to philosophical ideas of each thinker and how they understood and interpret war, the authors analyze the historic-political context in which these ideas emerged and what they proposed to avoid a nuclear disaster. Four Philosophers and the Bomb will be of interest to students and researchers of peace studies, international relations, political philosophy, and moral philosophy"-- Provided by publisher.
"Routledge Focus"--Cover.
Keywords: Russell, Bertrand, -- 1872-1970.; Jaspers, Karl, -- 1883-1969.; Aron, Raymond, -- 1905-1983.; Anders, Günther, -- 1902-1992.; Nuclear warfare -- Philosophy.; Nuclear warfare -- Moral and ethical aspects.; World politics -- 20th century.; elektronické knihy; electronic books